Industrial society and its future - Kaczynski, Theodore John, 1942-2023 (S.l. : Pub House Books, 2018)
"The psychology of modern leftism", "sources of social problems", "The nature of freedom", "The 'bad' parts of technology cannot be separated from the 'good' parts, ... De titels van de hoofdstukken maken nieuwsgierig, Kaczynski pleit voor een andere houding wat betreft het industriële tijdperk waarin we leven.